Food rejection in young children: Validation of the Child Food Rejection Scale in English and cross-cultural examination in the UK and France. (April 2019) - Rioux, Camille; Lafraire, Jérémie; Picard, Delphine; Blissett, Jacueline
Highlights: Very few studies have directly compared food rejection in children from different countries. Validity of the English version of the Child Food Rejection Scale was assessed. The Child Food Rejection Scale can be successfully used in the UK. We examined cultural differences in food rejection in the UK and France. UK children are less neophobic and picky than French children. Abstract: Although there are numerous studies examining food rejection (neophobia and pickiness), very few studies have directly compared these particular behaviors in children from different countries. Testing children from different countries is important for future research, as there are clear differences between European countries in early feeding practices and child fruit and vegetable consumption. In the present study we aimed to (i) validate the Child Food Rejection Scale in English and (ii) compare children's food neophobia and pickiness in the UK and France. To that aim, the Child Food Rejection Scale was first translated into English and its reliability and validity were assessed. Second, food rejection scores in a UK sample (n = 117) and in a French sample (n = 256) were directly compared to examine cross-cultural differences. Results showed that the Child Food Rejection Scale can be successfully used outside France. Moreover results revealed that UK children are less neophobic and picky than French children. These cultural differences can be useful to inform targeted interventions to change food related behaviors in these different populations.